Evaluation of Heat Irreversibility in a Thin Film Flow of Couple Stress Fluid on a Moving Belt - Samuel O. Adesanya; Ramosheuw S. Lebelo; K. C. Moloi (Advances in Mathematical Physics, 2018)
This article addresses the inherent heat irreversibility in the flow of a couple stress thin film along a moving vertical belt subjected to free and adiabatic surface. Mathematical analysis for the fluid-governing-equations is performed in detail. For maximum thermal performance and efficiency, the present analysis follows the second law of thermodynamics approach for the evaluation of entropy generation rate in the moving film. With this thermodynamic process, the interconnectivity between variables responsible for energy wastage is accounted for in the thermo-fluid equipment. Results of the analysis revealed the fluid properties that contribute more to energy loss and how the exergy of the system can be restored.